Implementasi Website Virtual Tour Sebagai Upaya Transformasi Digital Pengelolaan Monkey Forest, Bali - Christina Purnama Yanti; Theresia Hendrawati; Ni Luh Wiwik Sri Rahayu G; Dewa Ayu Putri Wulandari; I Dewa Gede Yudhistira Maha Prabawa (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2026)
Monkey Forest Ubud is a conservation-based tourist destination with great potential, yet it still faces limitations in the use of digital technology, particularly in providing interactive promotional materials. This community service initiative aims to support digital transformation through the implementation of a virtual tour website capable of enhancing the quality of tourism promotion and education. The implementation process includes preparation, system development, training and mentoring for managers, implementation, and evaluation. The developed website features 360° panoramic views, digital maps, educational content, multilingual support, and responsive design. The results of the activity indicate that the developed system provides an interactive and informative digital exploration experience. An evaluation using the User Experience Questionnaire (UEQ) with 50 respondents showed that all assessment aspects fell into the good to very good categories, with an average score above 2 on most scales. Additionally, the training activities successfully improved the managers’ digital literacy and self-reliance in managing the website. Thus, the implementation of this virtual tour website makes a tangible contribution to supporting digital-based tourism promotion, enhancing the user experience, and strengthening the sustainable management of tourist destinations.